FÔNONS ÓPTICOS DE PEROVSKITAS DUPLAS Ca₃Mn₂B O₉ (B = W e Nb) - Martins Júnior, Antonio Luiz (2013)
In recent years, researchers and scientists has been devoted more to the study of inorganic materials, in particular the oxides known as perovskites, because its technological use. The analysis of their properties have been made by various techniques, among these we can mention the Raman spectroscopy and infrared, which show very sensitive to changes in the structure of these oxides. Thus, this work presents the study of phonons at room temperature the double perovskites Ca₃Mn₂WO₉ (CMWO) and Ca₃Mn₂NbO₉ (CMNO) by means of Raman scattering techniques and transmittance Infrared. Both compounds crystallize in a monoclinic system space group P2₁/n, with Z = 2. The Raman and infrared spectra are interpreted by the group factor analysis in terms of the space group P2₁/n. Also the vibrational modes of stretching and folding B were reported "- O. The observed spectra are very similar to the cubic perovskite structure prototype dual Fm3m indicating that the phases of the study result of minor distortions cubic cell. It is also observed an unexpected band in the Raman spectra of both materials. We suggest that this additional bandwidth would result from occupational disorder of the sites of the cation B, which is evidenced in both phases.